Вплив тиску на структуру і властивості композитів алмаз-Fe-Cu-Ni-Sn-CrB2, отриманих гарячим пресування - Бондаренко, М.О.; Мечник, В.А.; Ткач, С.В.; Супрун, М.В.; Казьмін, О.О. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The paper investigates the structure and the mechanic features of composite system diamond-Fe-Cu-Ni-Sn-CrB2, was sintered in a muffle furnace. The research determine, that a building of metal zone near the diamond has got a fundamental differences against building matrix zone far from the diamond. The causes of this phenomenon was explained.